The Effectivity of Module for The Basic Technical Skills of Volleyball Class VII Junior High School in Alian District of Kebumen Regency (Indonesian Journal for Physical Education and Sport, 2021)
The game of volleyball requires coordination of motion to perform all the movements that exist in the game bolavoli. This study aims to develop a basic volleyball technique learning module for grade VII students in Alian Subdistrict of Kebumen Regency and assess the feasibility level of the learning module before it is used as a learning medium. This research is R&D research with 4D development model. The development procedure used includes 4 stages, namely preliminary study, development, field trials and dissemination. This learning module was validated by 2 material experts, 1 media expert, then tested on 106 students consisting of SMP Ma'arif 2 Alian, SMP Negeri 1 Alian, MTSS Kaudlul Ulum, and SMP Negeri 2 Satu Atap Alian. The results showed that this learning module as a whole is worthy as a teaching material. This is indicated by the validation results performed by media experts are said to be very feasible with a percentage of 89.7%. According to materials experts, this learning module is feasible with a percentage of 86.5%. Based on the data analysis of field trial results obtained very feasible criteria with percentages of 92% and 85%. From these results, it can be concluded that the Basic Technical Learning Module of Volleyball is very feasible to be used as a learning medium in the subjects of Grade VII Junior High School Penjasorkes in Alian Subdistrict, Kebumen Regency.